Tahlīliyah al-Nassiyyah ‘an al-Sabaki al-Nahwiyyi fī Sūrah al-Qasaṣ - Qurrota Aulia Zahra (Journal of Arabic Literature (JaLi), 2020)
The grammatical cohesion is very important in the discourse because it relates to the meaning that will be produced. Therefore, the researcher would like to explore the grammatical cohesion in surat al-Qashash, which becomes an essential element that binds the semantic structure of a discourse. The grammatical cohesion devices can take the forms of intangible reference, substitution, ellipsis and conjunction.The problems investigated in this study include: the types of grammatical cohesion devices and in surah al-Qasas. Second, the types of grammatical devices contained in surah al-Qasas. This research uses descriptive qualitative method with content analysis approach and focuses on the grammatical cohesion devices contained in surah al-Qasas.The study found four types of grammatical cohesion devices namely reference, substitution, ellipsis and conjunction in the form of dhomir, words, phrases or sentences as a reference between two sentences in pairs.